THE ROLE OF DIGITAL BANKING SOLUTIONS IN ENHANCING CUSTOMER ACQUISITION AND RETENTION IN COMPETITIVE MARKETS - Mark Osemedua Nwaozomudoh (PT. Antis International Publisher, 2024)
Objective: This study examines the role of digital banking solutions in enhancing customer acquisition and retention in competitive markets, with a focus on ALAT Bank and Moniepoint in Nigeria. It aims to bridge the knowledge gap regarding the impact of specific digital marketing strategies—such as social media, email marketing, mobile app promotions, and online ads—on customer behavior in emerging markets like Nigeria. Method: A mixed-methods approach was adopted, combining both quantitative and qualitative data to ensure a comprehensive analysis. Structured questionnaires were distributed to 600 respondents, evenly split between ALAT Bank and Moniepoint. A descriptive-causal research design was employed to investigate the relationships between various marketing strategies and customer behavior. Result: The findings indicate that social media marketing is the most effective strategy for customer retention, with ALAT Bank achieving a higher retention rate (65%) than Moniepoint (58%) due to more targeted and consistent campaigns. Email marketing significantly contributes to Moniepoint’s retention (35%), while mobile app promotions show moderate effectiveness, with Moniepoint (28%) slightly outperforming ALAT Bank (25%). Online ads, however, have minimal impact on customer retention, highlighting their limited role in fostering long-term customer relationships. Novelty: This research fills a crucial gap by providing empirical insights into how digital marketing strategies influence customer acquisition and retention in Nigeria’s banking sector. It offers actionable recommendations for banks to optimize their digital marketing efforts, emphasizing the importance of personalized social media engagement, mobile-first strategies with integrated rewards, and enhanced email campaign personalization. Additionally, it highlights the need for more interactive and targeted advertising approaches to improve customer engagement in competitive and dynamic markets.